1985
DOI: 10.1210/jcem-61-1-98
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptors in Human Growth Hormone and Prolactin- Secreting Pituitary Adenomas

Abstract: [125I-Tyr]Somatostatin [( 125I-Tyr]SRIH) binding was found in 11 GH-secreting pituitary adenomas [Kd = 0.46 +/- 0.15 (+/- SE) nM; maximum binding, 165 +/- 35 fmol/mg protein). This binding was specific, since it was displaced by somatostatin-14 (SRIH-14), N-Tyr-SRIH-14, and SRIH-28. In contrast, a number of peptides and drugs not structurally related to SRIH, such as bombesin, dopamine, LHRH, met-enkephalin, naloxone, neurotensin, secretin, substance P, TRH, or vasoactive intestinal peptide, did not affect [12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…1). They were characterized by different groups [10][11][12], As the other authors, we found that the density of SRIH receptors was highly vari able among the different adenomas tested. However, in our study, we found an inverse correlation between the number of SRIH receptors and the plasma GH levels ( fig.…”
Section: Trh Receptorssupporting
confidence: 75%
See 1 more Smart Citation
“…1). They were characterized by different groups [10][11][12], As the other authors, we found that the density of SRIH receptors was highly vari able among the different adenomas tested. However, in our study, we found an inverse correlation between the number of SRIH receptors and the plasma GH levels ( fig.…”
Section: Trh Receptorssupporting
confidence: 75%
“…It has not been demon strated that SRIH or SRIH analogues were able to reduce in vivo PRL secretion [13]. However, recently, an in vitro inhibition of PRL secretion from human adenoma tous and normal lactotropes has been demonstrated [ 14], We found high-affinity SRIH-binding sites on the mem branes of PRL-secreting adenomas with characteristics similar to those obtained on GH-secreting adenoma membranes [11]. However, the number of binding sites was 4 times lower than that found in GH-secreting ade nomas (Bmax = 37 ± 9 fmol/mg protein) and there was no correlation between the density of SRIH-binding sites and the plasma PRL levels.…”
Section: Trh Receptorssupporting
confidence: 73%
“…In analogy, a similar mechanism of somatostatin may exist in the pituitary. For the investigation of the mechanism of somatostatin action in the pituitary, human GH-producing pituitary tumor cells are useful because the presence of somatostatin receptors in the cell membrane has been demonstrated (12)(13)(14) and the inhibition of GH secretion by somatostatin has been reported (15)(16)(17)(18)(19). In the present study we investigated the response of the membrane potential to somatostatin in dissociated human pituitary adenomas that secreted GH, and we found that somatostatin increased the K+ conductance.…”
Section: Introductionmentioning
confidence: 68%
“…3], In vitro studies of GH-secreting pituitary adenomas demon-stratcd a direct inhibitory effect of SRIH on GH secretion [4,5]. This effect is mediated through specific SRIH receptors characterized on rat somatotrophs [6] as well as on GH-secreting adenomas [7][8][9], The action of SRIH on pituitary somatotrophs is mediated through multiple mechanisms involving the inhibition of adenylate cyclase [10][11][12], the opening of K+ channels [13] and the subse quent closing of voltage-dependent Ca2+ channels [ 14], Originally, the variability of in vivo, as well as in vitro, GH response to SRIH in GH-secreting pituitary tumors [2,5,15] was attributed to the very short half-life of the native peptide. The development of potent long-acting SRIH analogs was of major importance in the treatment of acromegaly [for review, see 16].…”
Section: Introductionmentioning
confidence: 99%